Validation of content of a rubric to evaluate the oral competence of a foreign language from the socioformative approach - Mounkoro, Ismaila (2019)
This research arises from the lack of tools to qualify the oral competence of a foreign language. That is relevant to the bets of the knowledge society subject to the socioformative approach. The purpose was to validate the content of a tool to qualify the oral competence of a foreign language at level B1. An instrumental study was used according to the following stages: 1) development of a tool through a socioformative type scheme; 2) review and improvement of the tool by three experts; 3) validation of content by a jury of 16 experts in the field. The results obtained indicate that the tool is suitable for qualifying the oral competence of a foreign language, with an Aiken V higher than V 0.75. The initial reliability was 0.842. Conclusions: the rubric is adequate; however, it must be implemented to a wider public in order to define the construct validity.